2018
DOI: 10.1042/bsr20180333
|View full text |Cite
|
Sign up to set email alerts
|

The role of perineural invasion in penile cancer: a meta-analysis and systematic review

Abstract: The significance of perineural invasion (PNI) present in penile cancer (PC) is controversial. In order to clarify the predictive role of PNI in the inguinal lymph node (ILN) metastases (ILNM) and oncologic outcome of patients, we performed this meta-analysis and systematic review. The search of PubMed, Embase, and Web of Science was conducted for appropriate studies, up to 20 January 2018. The pooled odds ratio (OR) and hazard ratio (HR) with their 95% confidence interval (CI) were applied to evaluate the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…They also added higher neutrophil-to-lymphocyte ratios (NLR) and squamous cell carcinoma antigen (SCC-Ag) overexpression to the above list of biochemical predictors (23). Zhou et al performed a meta-analysis of exclusively perineural invasion and its ability to predict inguinal lymph node metastasis; they showed a statistically significant higher rate of LNM in penile SCC with perineural invasion compared to that in which nerve invasion is absent (25).…”
Section: Pertinent Meta-analysesmentioning
confidence: 99%
“…They also added higher neutrophil-to-lymphocyte ratios (NLR) and squamous cell carcinoma antigen (SCC-Ag) overexpression to the above list of biochemical predictors (23). Zhou et al performed a meta-analysis of exclusively perineural invasion and its ability to predict inguinal lymph node metastasis; they showed a statistically significant higher rate of LNM in penile SCC with perineural invasion compared to that in which nerve invasion is absent (25).…”
Section: Pertinent Meta-analysesmentioning
confidence: 99%
“…9 Yet differing outcomes between studies warrant validation of the role of LVI as an independent prognostic indicator of reduced survival in patients with penile carcinoma. 9 Studies have demonstrated clinicopathological variables, such as inguinal lymph node metastases, perineural invasion, tumor stage, and grade, to be predictors of poor survival [10][11][12] ; however, there are socioeconomic and psychosocial factors that influence survival risk. Demographic and socioeconomic predictors, such as lower education attainment, African-American, and Hispanic ethnicity, have been shown to be associated with poor survival.…”
Section: Introductionmentioning
confidence: 99%
“…The data presented in this work demonstrate that miR-145 is a potential biomarker of perineural invasion (PNI). In previous studies, PNI has been recognized as a prognostic indicator of poor survival in patients with PC (27). The downregulation of miR-145 is associated with poor PFS (progression-free survival) in patients with lung cancer, colorectal cancer, esophageal cancer, breast cancer, and glioma (28).…”
Section: Discussionmentioning
confidence: 99%